Toxicity of Adjuvant Radiotherapy in Patients with Breast Cancer: A Review Study - Shahid Sales, Soodabeh; Avan, Amir; Javadinia, Seyed Alireza; Dehghani, Mansoureh; A. Ferns, Gordon (Reports of Radiotherapy and Oncology, 2019)
Conservative treatment in early-stage breast cancer is considered a standard approach. Breast preserving surgery with adjuvant radiotherapy is as effective as mastectomy in the early stages of breast cancer to control local disease and distant metastasis and maintain the overall survival rate. Minimally invasive surgery for the treatment of axillary spread and new techniques of breast preservation surgery will probably lead to a reduction in mastectomy-related complications. However, the complications of adjuvant radiotherapy remain a challenge. Cutaneous, cardiac, and pulmonary toxicity are the main complications of adjuvant breast irradiation. The multidisciplinary features (systemic treatment, endocrine therapy, and surgery), patient profile (history of underlying diseases, age, and habits), and irradiation-associated parameters are the factors affecting safe adjuvant radiotherapy. Advances in irradiation techniques and facilities related to the preservation of organs at risk (such as IGRT, tracing and tracking systems, and respiratory gating) are modern tools for reducing the risk of toxicity. Reported data from clinical trials or retrospective surveys greatly help physicians in consulting the patients on the efficacy and potential side effects of treatment and leads to the improvement of the decision making process.